Recenzja monografii: Р.В. Белютин, Прагмасемантические и лингвоментальные проекции немецкого спортивного дискурса, Смоленск: Издательство СмолГУ, 2019. 336 s. ISBN 978-5-88018-641-9 - Narloch, Andrzej (Scripta Neophilologica Posnaniensia, 2021)
Book review: Belyutin, R.V. 2019. Pragmasemantic and linguomental projections of German sports discourse. Smolensk: SmolSU Publishing House. 336 pp. ISBN 978-5-88018-641-9.